First two unrelated cases of isolated sedoheptulokinase deficiency: A benign disorder?. Issue 5 (3rd February 2015) - Wamelink, Mirjam M. C.; Ramos, Ruben J. J. F.; den van Elzen, Annette P. M.; Ruijter, George J. G.; Bonte, Ramon; Diogo, Luisa; Garcia, Paula; Neves, Nelson; Nota, Benjamin; Haschemi, Arvand; Tavares de Almeida, Isabel; Salomons, Gajja S.
Abstract: We present the first two reported unrelated patients with an isolated sedoheptulokinase (SHPK) deficiency. The first patient presented with neonatal cholestasis, hypoglycemia, and anemia, while the second patient presented with congenital arthrogryposis multiplex, multiple contractures, and dysmorphisms. Both patients had elevated excretion of erythritol and sedoheptulose, and each had a homozygous nonsense mutation in SHPK . SHPK is an enzyme that phosphorylates sedoheptulose to sedoheptulose‐7‐phosphate, which is an important intermediate of the pentose phosphate pathway. It is questionable whether SHPK deficiency is a causal factor for the clinical phenotypes of our patients. This study illustrates the necessity of extensive functional and clinical workup for interpreting a novel variant, including nonsense variants.